Roles of O-GlcNAcylation on amyloid-β precursor protein processing, tau phosphorylation, and hippocampal synapses dysfunction in Alzheimer's disease. (1st February 2016) - Zheng, Bo-Wen; Yang, Li; Dai, Xue-Ling; Jiang, Zhao-Feng; Huang, Han-Chang
Abstract : Alzheimer disease (AD), a central nervous system degenerative disease, is characterized by abnormal deposition of amyloid-β peptide (Aβ), neurofibrillary tangles formed by hyperphosphorylated tau and synaptic loss. It is widely accepted that Aβ is the chief culprit of AD. Aβ peptide is the cleavage product of amyloid-β precursor protein (APP). Recently, more attention has been paid to O-linked β-N-acetylglucosaminylation (O-GlcNAcylation) modification of protein. O-GlcNAcylation plays a significant role in hippocampal synaptic function. Abated O-GlcNAcylation might be a modulator in progression of AD through regulating activity of pertinent enzymes and factors. Evidence suggests that enhanced O-GlcNAcylation interacts with tau phosphorylation and prevents brain from tau and Aβ-induced impairment. Here, we review the roles of O-GlcNAcylation in APP cleavage, tau phosphorylation and hippocampal synapses function.